A time for greater investment into care for pregnancy and heart disease. (15th October 2016) - Cauldwell, Matthew; Patel, Roshni; Steer, Philip; Gatzoulis, Michael
Abstract: Adult Congenital Heart Disease (ACHD) complicating pregnancy remains a relatively new and evolving field. An acceptance by paediatric cardiologists of the importance of working alongside their colleagues dealing with adult care as their patients get older is vital to ensure that these patients are provided with seamless continuity of care. One might have expected that as ACHD cardiologists increasingly forge ties with obstetricians who manage high risk pregnancy so that together they provide care for their mutual patients, we would see the mortality and morbidity of pregnancy in women with heart disease decline. Sadly this is yet to be the case and cardiac disease remains the leading single indirect cause of maternal death in the developed world. These disappointing figures should act as wake up call not only to the profession but also to those involved in commissioning and funding such services. Some progress has been made improving the outlook for many women with complex congenital heart disease as they consider embarking upon pregnancy. However, concerns still exist in relation to young patients being lost to follow-up and presenting pregnant without appropriate counselling and optimization of their cardiac condition. Furthermore it is unclear whether there is currently adequate workforce planning to deliver enough trained specialists who have the expertise to work in this area in the future. We submit herewith that further investment is essential if we wish to see improvements in the care of women with heart disease in relation to pregnancy.